PENERAPAN NILAI KARAKTER PEDULI SOSIAL SISWA MELALUI KEGIATAN JUMAT BERBAGI SD N 4 KUTOHARJO - Saqya Aini Mazaya; Prasetyo, Singgih Adhi; Baedowi, Sunan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the "Jumat Berbagi" (Friday Sharing) program, analyze its impact on students' social care character, and identify the supporting and inhibiting factors at SD N 4 Kutoharjo. Character education is crucial in elementary school as it forms the foundation for future personality development. This research uses a qualitative descriptive approach with data collection techniques including observation, interviews with the principal, teachers, and students, and documentation. The results indicate that "Jumat Berbagi" is implemented through a structured process where students bring food and drinks to be distributed to the local community and social institutions. This activity significantly impacts students' character by fostering empathy, sympathy, and a willingness to help others without expecting anything in return. Supporting factors include high enthusiasm from students and support from parents and school staff, while inhibiting factors include occasional logistical challenges and varying levels of initial student understanding. Overall, the program effectively internalizes the valu